Developing of National Accreditation Model for Rural Health Centers in Iran Health System. - Jafar Sadegh Tabrizi; Farid Gharibi; Samereh Pirahary (Tehran University of Medical Sciences, 2013)
The primary health care has notable effects on community health and accreditation is one of the appropriate evaluation methods that led to health system performance improvement, therefore, this study aims to developing of national accreditation model for rural health centers in Iran Health System.Firstly the suitable accreditation models selected to benchmarking worldwide via systematic review, the related books and medical university's web site surveyed and some interviews hold with experts. Then the obtain standards surveyed from the experts' perspectives via Delphi technique. Finally, the obtainedmodel assessedvia the experts' perspective and pilot study.The researchers identified JCAHO and CCHSA as the most excellent models. The obtained standards and their quality accepted from experts' perspective and pilot study, and finally the number of 55 standards acquired.The designed model has standards with acceptable quality and quantity, and researchers' hopeful that its application in rural health centers led to continues quality improvement.